Molecular characterization of Ornithobacterium rhinotracheale strains isolated from chickens in the Northwestern Iran - Ezdiyadi, Mehdi; Khosropanah, Mohammad Karim; Banani, Mansoor; Ghadimipour, Rahim; Davari, Kambiz (Veterinaria Italiana, 2022)
Ornithobacterium rhinotracheale is the etiological agent of chickens and turkeys’ respiratory diseases, reduction of eggs, growth retardation, and death. Present research aimed to conduct the isolation, recognition, and molecular investigations of the bacterium in commercial broiler chicken flocks in East Azerbaijan province, Northwest of Iran, by the partial sequencing of 16S rRNA gene, ERIC‑PCR, and RAPD‑PCR with the OPG11 and M13 primers. We obtained 330 specimens from tracheal swabs of 33 slaughtered broiler flocks, of which we found 14 isolates (4.24%) of five flocks (15.15%) to be O. rhinotracheale. Typing by RAPD assay with the OPG11 primer, and ERIC‑PCR, classified the isolates in two types of 1 and 2 molecular patterns, most of which belonged to type 1. However, the M13 primer‑based RAPD technique was inappropriate for distinguishing and categorizing the isolates and generating all of them in the same pattern. In a phylogenetic analysis of O. rhinotracheale based on 16S rRNA sequences, the strains generated three clusters (I‑III), in which all of the studied isolates fell in one cluster (cluster I). Based on the results obtained from the RAPD and ERIC‑PCR assays, the genetic patterns of broiler‑chicken‑isolated O. rhinotracheale strains in Northwestern Iran had no significant differences.